2008
DOI: 10.1021/jp801824g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Nanostructured Pd−Mo Electrocatalysts for Oxygen Reduction Reaction in Fuel Cells

Abstract: Carbon-supported Pd 100-x Mo x (0 e x e 40) nanoparticles have been synthesized by a simultaneous thermal decomposition of palladium acetylacetonate and molybdenum carbonyl in an organic solvent (o-xylene) in the presence of Vulcan XC-72R carbon, followed by heat treatment up to 900 °C in H 2 atmosphere and characterized chemically and structurally. X-ray diffraction data reveal the formation of single-phase facecentered cubic solid solutions for 0 e x e 30 after heat treating at 900 °C and the occurrence of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
67
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 29 publications
5
67
0
2
Order By: Relevance
“…Recently, Pd-based alloys have drawn much attention as they exhibit promising activity for ORR [17][18][19][20]. However, Pt-Pd bimetallic alloys have not been explored extensively.…”
mentioning
confidence: 99%
“…Recently, Pd-based alloys have drawn much attention as they exhibit promising activity for ORR [17][18][19][20]. However, Pt-Pd bimetallic alloys have not been explored extensively.…”
mentioning
confidence: 99%
“…At first, the metal precursor and carbon support were mixed together and refluxed and finally dried, followed by a heat treatment up to 900 C in H 2 atmosphere. 82 …”
Section: Thermal Decomposition Methodsmentioning
confidence: 99%
“…Specifically, the Pd 9 Au and Pd 4 Pt nanowires possess ORR activities of 0.49 and 0.79 mA cm -2 , which are larger than the analogous value from commercial Pt nanoparticles (0.21 mA cm -2 ). Recent studies have demonstrated that Pd catalysts can produce high ORR activity when combined with appropriate transition metals, such as Co, Fe, Mo, etc [59,61,98]. By an organic phase reaction of [Pd(acac) 2 ] and thermal decomposition of [Fe(CO) 5 ] in a mixture of oleyamine and octadecene at 160°C, Li et al [73] synthesized PdFe nanorods (PdFe-NRs) with tunable length.…”
Section: Introductionmentioning
confidence: 99%